Computational fluid dynamics simulation of a designed envelop contenting phase change material and imposed solar heat flux and ambient air. (February 2023) - Yan, Gongxing; Teng, Bin; Abed, Azher M.; Deifalla, Ahmed; Youshanlouei, Hossein Mehdizadeh; Abdulghani, Zuhair R.; Moria, Hazim
Abstract: Buildings are one of the largest consumers of energy for cooling and heating systems to provide the comfort temperature for human living. The use of smart materials or phase change materials (PCMs) pave the road to prevent heat loss of buildings. This material is injected into a block called envelop, employed in Buildings' roof and floor. In the present study, a envelop filled PCM with a melting temperature of 16.5 ° C was designed and simulated by computational fluid dynamic (CFD) and was imposed surrounding air (robin boundary condition). Moreover, the effects of Buoyant force, creating free convection mechanism due to melting PCM and density change with temperature, was considered in this numerical method. Thus, this unsteady numerical study focused on three inclined angles (30 ≤  θ  ≤ 60) and three solar heat flux ( 200 ≤ q " ≤ 300 W m 2 ) imposed in 12 h, whose effects were analyzed on the melting fraction, temperature contours for 12 h and melting fraction percentage at passing time after 12 h. The obtained results showed that the phase change line was perpendicular to gravity vector due to high buoyant force. Moreover, investigation of inclined angles was a vital parameter in PCM melting process. Furthermore, the indoor of building was safe from hot air outdoor at least 9 h exposing the worst solar heat flux. Highlights: Designing a envelop filled phase change material to cool the building indoor. Simulation of PCM with considering realistic boundary condition inducing air velocity, solar heat flux, natural convection of indoor building. The most melting PCM occurs in the top half of envelop due to hot air and heat solar flux of outdoor condition. The phase change line is perpendicular to gravity vector due to high buoyant force. The isotherms are parallel the top half of envelop due to high convective heat transfer.